2016
DOI: 10.1002/acr.22850
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Change and Minimal Important Differences of the LupusQoL in Patients With Systemic Lupus Erythematosus

Abstract: ObjectiveAs a health‐related quality of life (HRQOL) measure, the LupusQoL is a reliable and valid measure for adults with systemic lupus erythematosus (SLE). This study evaluates the responsiveness and minimal important differences (MIDs) for the 8 LupusQoL domains.MethodsPatients experiencing a flare were recruited from 9 UK centers. At each of the 10 monthly visits, HRQOL (LupusQoL, Short Form 36 health survey [SF‐36]), global rating of change (GRC), and disease activity using the British Isles Lupus Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
3
44
2
1
Order By: Relevance
“…The results of the association between disease activity and HRQoL may be altered by the choice of different disease activity measures, as has been shown in several observational studies and clinical trials. For instance, McElhone et al (10) found that little to no change was identified by HRQoL questionnaires when disease activity (measured by the British Isles Lupus Assessment Group index) worsened, while slightly higher consistency was reflected by these questionnaires when disease activity improved. In a post hoc analysis of the phase III belimumab trials, Furie et al showed that improvement in disease activity, as determined by the SLE Responder Index (SRI) response in patients with active disease, was associated with improvements in clinical, laboratory, and HRQoL measures.…”
Section: Evaluation Of Hrqol Measures In Slementioning
confidence: 99%
See 4 more Smart Citations
“…The results of the association between disease activity and HRQoL may be altered by the choice of different disease activity measures, as has been shown in several observational studies and clinical trials. For instance, McElhone et al (10) found that little to no change was identified by HRQoL questionnaires when disease activity (measured by the British Isles Lupus Assessment Group index) worsened, while slightly higher consistency was reflected by these questionnaires when disease activity improved. In a post hoc analysis of the phase III belimumab trials, Furie et al showed that improvement in disease activity, as determined by the SLE Responder Index (SRI) response in patients with active disease, was associated with improvements in clinical, laboratory, and HRQoL measures.…”
Section: Evaluation Of Hrqol Measures In Slementioning
confidence: 99%
“…SF-36 MCID definitions by Strand and Crawford (12) were based on patient-reported changes in the Guyatt "feeling thermometer" (27) in an RCT and are currently being used to identify patients with clinically important changes in RCTs. Devilliers et al and McElhone et al have derived MCID definitions for the SF-36 and, more importantly, for the LupusQoL (10,11), based on longitudinal observational studies. This study is the first to compare the performance of different MCID definitions in the SF-36 and LupusQoL.…”
Section: Evaluation Of Hrqol Measures In Slementioning
confidence: 99%
See 3 more Smart Citations